A Synthetic View on Haedoxans and Related Neolignans From Phryma leptostachya - Chen, Yang; Xiao, Shu; Huang, Jian; Xue, Wei; He, Shuzhong (Frontiers in Chemistry, 2020)
Haedoxans are a series of sesquilignan natural products isolated from the traditional insecticidal plant Phryma leptostachya. Given their significant insecticidal activity, haedoxans and related analogs have been considered as potential agents for plant defense. Moreover, these compounds also exhibit promising antifungal, antibacterial, and anticancer activities. The present paper is a review on the structure, biological activity, and mainly on the chemical synthesis of naturally occurring haedoxan-like molecules.